Synthesis of Hierarchical Porous Sulfur/Polypyrrole/Multiwalled Carbon Nanotube Composite Cathode for Lithium Batteries - Zhang, Yongguang; Zhao, Yan; Bakenov, Zhumabay; Tuiyebayeva, Madina; Konarov, Aishuak; Chen, P. (Electrochimica Acta, 2014)
Abstract A novel porous sulfur/polypyrrole/multiwalled carbon nanotube composite (S/PPy/MWNT) was synthesized via in situ polymerization of pyrrole monomer with nano-sulfur and MWNT aqueous suspension followed by a low temperature heat-treatment. Scanning electronic microscopy revealed the formation of a highly hierarchical mesoporous and macroporous structure. High resolution transmission electronic microscopy confirmed homogeneous dispersion of S, PPy and MWNT in the composite. In this composite, polypyrrole with its high adhesion ability to MWNT acts as a conductive binder to connect sulfur and MWNT matrix, as well as absorbs polysulfides into its porous structure positively affecting the composite performance as a cathode in a Li/S cell. The resulting S/PPy/MWNT composite cathode exhibited greatly enhanced cyclability and delivered a reversible discharge capacity of 751 mAh g−1 after 100 cycles at 0.2C.
Keywords: Hierarchical porous structure; Lithium/Sulfur battery; Nanostructured sulfur cathode; Sulfur/Polypyrrole/Multiwalled carbon nanotube composite